Synthesis and photophysical properties of monomeric and dimeric halogenated aza-BODIPYs - Cinar, H. Seyma; Ozcelik, Sennur; Kaya, Kerem; Kutlu, Oznur Dulger; Erdogmus, Ali; Gul, Ahmet (ELSEVIER, 2020)
In this study, the effects of incorporation of halogen atoms at different positions and dimerization on the photophysical properties of the aza-BODIPYs were investigated. Aza-BODIPY derivative carrying chlorine atoms on the para-position of the distal phenyl groups (4) and its core-brominated analogue (5) were prepared to establish the external and internal heavy atom effects. Dimerization of aza-BODIPY 4 through oxidative homocoupling with FeCl3 yielded the target homonuclear aza-BODIPY dimer (6). All of the aza-BODIPY derivatives prepared in this study were fully characterized by using UV-Vis, Fluorescence, NMR (H-1, C-13, B-11 and F-19), Mass and X-Ray spectroscopy techniques. The photophysical properties were fully characterized and compared to those of the tetra-phenyl aza-BODIPY derivative (A). Singlet oxygen generation experiments were also performed. The aza-BODIPY derivative possessing bromine atoms at the central core displayed the utmost efficiency for singlet oxygen generation. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Aza-BODIPY; Photophysics; Singlet oxygen generation; PDT; Bromination; HEAVY-ATOM; CRYSTAL-STRUCTURE; FACILE SYNTHESIS; EXCITED-STATE; IN-VITRO; DYES; PHOTOSENSITIZERS; AZADIPYRROMETHENE; PHTHALOCYANINE; Chemistry